PRELIMINARY ANALYSIS OF THE ROCK ART FROM BURACAS DA SERRA, ALVAIÁZERE (PORTUGAL) - Figueiredo, Alexandra; Coimbra, Fernando; Monteiro, Cláudio; Ribeiro, Nuno (Revista Cuadernos de Arte Prehistorico, 2021)
This article aims to make public the archaeological site Buracas da Serra (municipality of Alvaiázere), which reveals the presence of a possible engraving of astral character, contributing to the understanding of Late Prehistory and Protohistory in the region. The first archaeological information mentioning the existence of rock art in this area was presented by Alexandra Figueiredo, on a report regarding archaeological work in the dolmen Anta I de Rego da Murta (Rego da Murta, Alvaiázere), in 2003 (Figueiredo, 2003), and developed in a deeper way during the presentation of a PhD thesis, in 2007 (Figueiredo, 2007), mentioning the existence of prehistoric art in the municipality of Alvaiázere, namely engravings and possible paintings on Anta I do Rego da Murta and engravings on the menhir of the same megalithic complex. After this work, archaeological interventions carried out in Alvaiázere and visits to new sites have enabled to reference more traces observed in cave context or on horizontal outcrops located in open spaces, connected with the mentioned megalithic complex or with the Alvaiázere Sierra. These discoveries have led to the proposal of a research project directed to the cavities of the Nabão river (2010- 2011), integrated in the project PNTA ANTROPE – Anthropization of spaces – forms of adaptation of the natural resources and continuity of human occupations in Prehistory-and Protohistory in Extremadura (Portugal). One of the recorded sites was an engraving of astral typology, in the site Buracas da Serra. This figure appears isolated, in a cavity oriented to the East. The present symbolism, the carving technique and the proximity to some archaeological sites allows assigning it, chronologically, to a period between Late Prehistory and Protohistory.